Impact of providing psychiatry specialty pharmacist intervention on reducing drug‐related problems among children with autism spectrum disorder related to disruptive behavioural symptoms: A prospective randomized open‐label study. (20th March 2017) - Wongpakaran, R.; Suansanae, T.; Tan‐khum, T.; Kraivichian, C.; Ongarjsakulman, R.; Suthisisang, C.
Abstract : Summary: What is known and objectives: Psychopharmacologic therapy has so far focused on ameliorating disruptive behaviours to improve patient's function and quality of life. Due to the complicated neurobiological aetiology of autism spectrum disorder (ASD), a traditional pharmacist intervention may be insufficient to initiate the optimal care for this vulnerable population. We evaluate the impact of providing specialty psychiatry (PS) pharmacist intervention in identifying and resolving drug‐related problems (DRPs) among children with ASD associated with disruptive behaviours. Methods: An eight‐week‐long, prospective, randomized open‐label study was conducted. Children between 2.5 and 12 years of age with ASD and showing disruptive behaviours were included. They were randomly assigned to an intervention or a control group. Patients in the intervention group received pharmacist interventions delivered by a PS pharmacist, while those in control group were cared by a hospital pharmacist. The primary outcome was the number of patients who resolved of at least one DRP by the end of the study. The secondary outcome was to compare the mean Aberrant Behavior Checklist‐Irritability (ABC‐I) scores between the two groups. Results: Twenty‐five patients were randomly assigned to either an intervention or control group. At week 8, the total number of patients who resolved of at least one DRP was 13 (52%) in the intervention group and 4 (16%) in the control group, respectively ( P =.016). Improper drug selection, medication non‐adherence and subtherapeutic dosage were the most common DRPs. Mean ABC‐I scores improved in the intervention group more than in the control group (9.8±5.6 vs 17.7±7.9; P <.001). What is new and conclusion: To the best of our knowledge, this is the first study which demonstrated that PS pharmacist intervention is an effective strategy to resolve DRPs in patient with ASD. The reduction in common DRPs mostly resulted from the PS pharmacist interventions, including selection of antipsychotic agent, adjustment of dosage based on ABC‐I scores and provision of individualized drug counselling. Reducing DRPs led to the improvement of any disruptive behaviour. In addition, multidisciplinary team should develop drug therapy protocols to promote the role of pharmacists in this setting. Abstract : This is the first study demonstrating the impact of psychiatry pharmacist on reducing number of drug‐related problems in patients with ASD when compared to usual care. Number of patients who resolved of at least one DRP in intervention group increased continuously from week 1 to 8 which showed statistically significant difference from control group at week 6 and 8.